Awareness on health insurance and health care costs among non-communicable disease patients attending a tertiary care centre - Jebamalar, J.; Kumar, P. K. Kailash (International Journal Of Community Medicine And Public Health, 2019)
Background: The silent epidemic of non-communicable diseases threatens to retard the progress towards curbing catastrophic health expenditure. The present study aimed to describe the level of awareness about and utilisation of health insurance and to measure the healthcare costs for non-communicable diseases. Methods: A total of 354 adult patients suffering from non-communicable diseases, who reside in Villupuram district and attend the NCD clinic in the Government medical college hospital, Villupuram were studied over a period of 6 months. Results: 77% of the subjects were aware of health insurance. The most frequent source of information was local government officials and the hospitals themselves. 74.01% had availed some form of health insurance. There was a moderately strong correlation between loss of wages and total health expenses. The incidence of catastrophic health expenditure due to NCD clinic visits was around 7%. Conclusions: The absence of outpatient costs in the covers of most health insurance schemes may be decreasing their effectiveness in controlling catastrophic health expenditure.